'There's no one way of doing things': Wildlife management and environmentality in Nunavik. Issue 4 (April 2019) - Gombay, Nicole
Abstract : Pressures on Inuit 'subsistence' activities have sources that are at once internal and external, be they at the scale of the individual or the nation, be they psychic or in response to the requirements of formal institutions of the state. With the ever-encroaching and interwoven connections between Inuit and settler colonial populations, the complexities of this dynamic are increasingly evident. As a result, one cannot write about Inuit subsistence without equally recognising how it is enmeshed with settler colonial populations and their institutions. Reflecting this dynamic, this paper uses the notion of environmentality to underscore some of the ways in which state-sponsored wildlife management in Nunavik is playing out and being perceived by a variety of actors in the region. In so doing, it discusses the ways in which Inuit and non-Inuit are participating in and resisting, accepting and rejecting governmental attempts to manage their practices.